The Inhibitory Effect of Poly (DMAA-co-MMA) on Bacteria, Yeast and Dermatophyte Fungi Which Cause Serious Illnesses in People - Sönmez, Pınar Erecevıt; Pıhtılı, Güzin; Kırbag, Sevda (My University, 2021)
In this study, it was researched the inhibitor effects of solutions including dichloromethane of poly dimethylacrylamide-co-methylmethacrylate P(DMAA-co-MMA) on microorganisms such as bacteria, yeast and dermatophyte fungi which cause serious illnesses in people. This solution, which was examined by the disc diffusion method, has antimicrobial feature upon preventing the proliferation of all bacteria (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus) and dermatophyte fungi except Bacillus megaterium and Klebsiella pneumoniae. In antimicrobial susceptibility data; poly P(DMAA-co-MMA) dissolved in dichloromethane has an inhibitory effect against the growth of yeast and dermatophyte fungi (on Candida spp. with 11.3 mm / inhibition area - 12.3 mm / inhibition area and 11.3 mm / inhibition area on Epidermophyton sp. - 11.3 mm / inhibition area on Trichophyton sp.) (P <0.001). MIC (Minimal inhibition concentration) breakpoints that strengthen the disk diffusion method are 50-100 ?L (4500– 9000 ?g in 10 mL) as the smallest value that inhibits the growth of bacteria, yeasts, dermatophyta. The antimicrobial compound can be of great advantage to illuminate future studies in this area. The polymer used in the study will provide a promising new addition to antimicrobial polymers that fight microorganisms that cause inflammation and fungal infections.
Keywords: New antimicrobial polymeric compound; Poly (DMAA-co-MMA); Inhibitory effect